Initial Stage COVID-19 Detection System Based on Patients' Symptoms and Chest X-Ray Images. Issue 1 (31st December 2022) - Attaullah, Muhammad; Ali, Mushtaq; Almufareh, Maram Fahhad; Ahmad, Muneer; Hussain, Lal; Jhanjhi, Nz; Humayun, Mamoona
ABSTRACT: The accurate diagnosis of the initial stage COVID-19 is necessary for minimizing its spreading rate. The physicians most often recommend RT-PCR tests; this is invasive, time-consuming, and ineffective in reducing the spread rate of COVID-19. However, this can be minimized by using noninvasive and fast machine learning methods trained either on labeled patients' symptoms or medical images. The machine learning methods trained on labeled patients' symptoms cannot differentiate between different types of pneumonias like COVID-19, viral pneumonia, and bacterial pneumonia because of similar symptoms, i.e., cough, fever, headache, sore throat, and shortness of breath. The machine learning methods trained on labeled patients' medical images have the potential to overcome the limitation of the symptom-based method; however, these methods are incapable of detecting COVID-19 in the initial stage because the infection of COVID-19 takes 3 to 12 days to appear. This research proposes a COVID-19 detection system with the potential to detect COVID-19 in the initial stage by employing deep learning models over patients' symptoms and chest X-Ray images. The proposed system obtained average accuracy 78.88%, specificity 94%, and sensitivity 77% on a testing dataset containing 800 patients' X-Ray images and 800 patients' symptoms, better than existing COVID-19 detection methods.